PENGARUH LINGKUNGAN KELUARGA DAN EFIKASI DIRI TERHADAP MOTIVASI BERWIRAUSAHA PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI JAKARTA - Siti Nur Aini; Dedi Purwana ES.; Ari Saptono (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2015)
This study aims to analyze the influence of family environment and self-efficacy on entrepreneurial motivation. The method used in this research was ex-post facto with correlational approach. The data was collected using questionnaires distributed to 74 students of Faculty of Economics, Universitas Negeri Jakarta. Path Analysis was used for analyzing the data. This study reveals that; 1) family environment directly affects entrepreneurial motivation (p=0.581); 2) self-efficacy directly influences entrepreneurial motivation (p=0.538), and 3) family environment directly affects self-efficacy (p=0.380). Keywords: entrepreneurial motivation, family environment, self-efficacy, path analysis